El gasto fiscal en Ecuador: factores que incidieron a partir de la dolarización. - Vasquez Parraga, Gema Stefania (My University, 2019)
This paper analyzes the fiscal expenditure from the dollarization in Ecuador by means of the classification of the total expenses, in such a way that it is possible to find what factors affected from the change of the currency, the statistical data of the Central Bank of Ecuador were taken, with the purpose of carrying out the respective analysis of the results, in which it is evident that for the Ecuadorian state it has been a source of development and economic growth, despite the fact that since dollarization there have been various limitations on issues of monetary policy, so it is understood that as a result there is the requirement of the adoption of strict fiscal policies to have a better economic development of the country.
El presente trabajo analiza el gasto fiscal a partir de la dolarización en el Ecuador mediante la clasificación de los gastos totales, de tal manera que permita encontrar que factores incidieron desde el cambio de la moneda, se tomaron los datos estadísticos del Banco Central del Ecuador, con la finalidad de realizar el respectivo análisis de los resultados, en el cual se evidencia que para el estado ecuatoriano ha sido una fuente de desarrollo y crecimiento económico, a pesar de que desde la dolarización se han dado diversas limitaciones en cuestiones de política monetaria, por lo que se entiende que como resultado está la exigencia de la adopción de políticas fiscales estrictas para tener un mejor desarrollo económico del país.
Keywords: GASTO FISCAL; GASTO CORRIENTE; GASTO DE CAPITAL; DOLARIZACIÓN; SECTOR PÚBLICO; INVERSIÓN